Development and Validation of the Pre- and Post-Processing Algorithms for Quantitative Gait Analysis using a Prototype Wearable Sensor System - Theron, Nicolaas J. (University of Pretoria, 2018)
Dissertation (MEng)--University of Pretoria, 2017.